The Contribution of the People of Souf in Building the Jordanian State - Al-Zu’riqat, Zaid Khaled; Zreqat, Dalal Ali (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to shed light on the contributions of the inhabitants of Souf to various institutions of the Jordanian state across political, economic, administrative, educational, and social contexts. These contributions have greatly influenced the development and progress of the Jordanian state. Methodos: The research adopted a descriptive analytical approach, encompassing two main directions. The first was theoretical, drawing on a range of sources and references to provide a comprehensive overview of Souf and its people since the establishment of the Emirate. The second direction was field-based, relying on local narratives. Results: The study discovered that Souf’s inhabitants made substantial contributions to nation-building during a critical and challenging period in the establishment of the Jordanian state, amidst complex economic, political, social, and demographic circumstances. Noteworthy contributions include the creation of the Souf government between the tenure of the Faisal government and the establishment of the East Jordan Emirate, with one of Souf’s residents assuming leadership. Souf’s inhabitants also played a pivotal role in fostering reconciliation among major Jordanian tribes following the tribal conflicts known as the "Harayib" era. Moreover, they actively participated during the internal security incidents of 1969-1970, resisting unlawful groups and preventing their entry into Souf. This resistance resulted in the sacrifice of seventeen martyrs who defended their town and homeland. In the agricultural economy, Souf’s inhabitants excelled in the dairy industry and were pioneers in establishing and exporting agricultural nurseries to Arab Gulf countries. Conclusion: The study concludes that the contribution of Souf’s inhabitants to the building of the Jordanian state was significant and multi-dimensional, spanning various levels and positively impacting the state’s formation, revival, and development processes.